What difference does it make? A laboratory experiment on the effectiveness of health-oriented leadership working on-site compared to the digital working context - Laura Klebe; Jörg Felfe (BMC, 2023)
Abstract Background Health-oriented leadership (HoL) represents an important workplace resource for employees. However, as opportunities to work from home increase, the question arises, whether leadership is more or less effective in digital working contexts compared to working on-site. Methods The current research investigates, whether the effectiveness of health-oriented leadership in terms of staff care is influenced by the working context. In a laboratory experiment with a 2 (no staff care vs. staff care) x 2 (working on-site vs. digital) mixed design (N = 60), a moderating effect of the working context on the relationship between staff care and employees' mental exhaustion, heart rate, heart rate variability, engagement and job satisfaction was tested. Results Results uncovered positive effects of staff care on employees' mental exhaustion and work-related attitudes in both conditions (d = 1.09-1.91). As expected, the results indicate that the effects on employees' engagement (d = 0.65) and job satisfaction (d = 0.72) are weaker when working digital. Conclusion Findings show that the effectiveness of staff care might differ between working on-site and working digital. In order to maintain the effectiveness of staff care, leaders and employees should keep regular face-to-face contact also when mainly working from home. The study ties in with research on digital leadership and leadership effectiveness, and contributes to the deeper understanding of situational contingencies of health-specific leadership during the process of digitization.